2020
DOI: 10.3390/met10101337
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Effect of Ultrafine SiC Additions on Corrosion and Wear Performance of Alumina-Silicon Carbide Composite Material Produced by SPS Sintering

Abstract: Alumina-silicon carbide (Al2O3–SiC) composites of varying compositions (15, 20, 25 and 30 vol.%)–SiC were produced by the ball milling of Al2O3 and SiC powders, followed by spark plasma sintering. The samples were sintered at a temperature and pressure of 1600 °C and 50 MPa, respectively, thermally etched at 1400 °C and mechanically fractured by hammer impact. The effect of SiC additions to monolithic Al2O3 on the densification response, microstructural and phase evolutions, and fracture morphologies were eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Bakhtiari et al [69] demonstrated in their study of ferrosilicon addition and the in-situ formation of SiC nano-whiskers on MgO-C refractories that the addition of ferrosilicon significantly increased the strength of the alloy. Mogale and Matizamhuka [70] observed that upon adding SiC to Al 2 O 3, the SiC grains were ingrained into the Al 2 O 3 . The study shows that Al 2 O 3 -SiC composite is an innovative material that could improve wear resistance with a volume percent above 15.…”
Section: Silicon As a Sustainable Reinforcement Materials As A Major ...mentioning
confidence: 99%
“…Bakhtiari et al [69] demonstrated in their study of ferrosilicon addition and the in-situ formation of SiC nano-whiskers on MgO-C refractories that the addition of ferrosilicon significantly increased the strength of the alloy. Mogale and Matizamhuka [70] observed that upon adding SiC to Al 2 O 3, the SiC grains were ingrained into the Al 2 O 3 . The study shows that Al 2 O 3 -SiC composite is an innovative material that could improve wear resistance with a volume percent above 15.…”
Section: Silicon As a Sustainable Reinforcement Materials As A Major ...mentioning
confidence: 99%